Chronic disease and sitting time in middle-aged Australian males: findings from the 45 and Up Study - George, Emma S.; Rosenkranz, Richard R.; Kolt, Gregory S. (My University, 2013)
Background: Compared to females, males experience a range of health inequities including higher rates of diabetes and cardiovascular disease. Although sitting time is emerging as a distinct risk factor for chronic disease, research on the association of sitting time and chronic disease in middle-aged Australian males is limited. Methods: A sample of 63,048 males aged 45-64 years was drawn from the baseline dataset of the 45 and Up Study – a longitudinal cohort study on healthy ageing with 267,153 participants from across New South Wales, Australia’s most populous state. Baseline data on self-reported chronic disease (heart disease, cancer, diabetes, high blood pressure, combined chronic diseases), sitting time, physical activity (Active Australia Survey), and a range of covariates were used for cross-sectional analyses. Crude (OR), partially and fully adjusted odds ratios (AOR) and 95% confidence intervals (CI) were calculated using binary logistic regression. Results: Compared to those sitting <4 hours/day, participants reporting 4 to <6, 6 to <8, and ≥8 hours were significantly more likely to report ever having any chronic disease (AOR 1.06, 95% CI 1.00 – 1.12, p = 0.050; AOR 1.10, 95% CI 1.03 – 1.16, p = 0.003; AOR 1.09, 95% CI 1.03 – 1.15, p = 0.002, respectively). Participants who reported 6 to <8 hours and ≥8 hours of sitting were also significantly more likely to report ever having diabetes than those reporting <4 hours/day (AOR 1.15, 95% CI 1.03 – 1.28, p = 0.016; AOR 1.21, 95% CI 1.09 – 1.33, p <0.001, respectively). Conclusions: Our findings suggest that higher volumes of sitting time are significantly associated with diabetes and overall chronic disease, independent of physical activity and other potentially confounding factors. Prospective studies using valid and reliable measures into domain-specific sitting time in middle-aged males are required to understand and explain the direction of these relationships.
Keywords: Physical activity; Sedentary behaviour; Sedentary lifestyle; Chronic disease; Heart disease; Cancer; Diabetes; Blood pressure